ACUTE TOXICITY AND BEHAVIOURAL RESPONSES OF CYPERMETHRIN TO THE FISH Anabas testudineus - JHA, AMIT KUMAR; ., ANUPAMA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Cypermethrin a fourth generation pyrethroid was used for this investigation to study the acute toxicity and behavioural responses to the fish Anabas testudineus (Bloch). This fish is locally known as “Kabai” and very abundantly found in the wetlands and water reservoirs of Mithila region but tremendous use of pesticides in agriculture sector is adversely affecting the aquatic fauna especially the fishes. The wide use of pesticides not only damaging the fish fauna living in aquatic bed but also put lethal and sublethal impact on human beings due to consumption of pesticides affected fish. The acute toxicity of cypermethrin to the test fish was determined for 24, 48, 72 and 96 hours. The LC50 value determined by regression equation was 0.15 ppm, 0.20 ppm, 0.25 ppm and 0.30 ppm respectively. The sublethal concentration was determined 0.106 ppm fishes that were exposed to different concentrations of cypermethrin exhibited exciting and agonistic behaviour. Restlessness, erratic opercular movement difficulty in respiration and convulsions were observed also. The fish came to the surface again and again possibly to gulp the atmospheric air directly and to avoid the toxic environment. Air bubbles were noticed coming out of the mouth. These hyperactive response were marked at higher concentrations and that too in the earlier phase of exposure. However, in the later stage of exposure, the affected fish showed hypoactivity lying for several hours on the side of the bottom of aquaria making very little movement. Another characteristic behavioural change was that some fishes frequently dashed against the walls of the experimental aquaria. Such affected fish at times swam with head downwards jabbing and scraping at the bottom with the snout. This behaviour was quite apparent during later phase of exposure and continued until the fish became quiescent just before death.